Invasive pneumococcal disease in children - a case report of pneumonia with pleural effusion and septicemia - Pekmezović, Slađana; Blagojević, Svetlana; Jašović, Bojan; Čotrić, Vladimir; Pejović, Janko; Mutavdžić Divac, Slavica (PONS - medicinski časopis, 2026)
Slađana Pekmezović1,4, Svetlana Blagojević1, Bojan Jašović3,4, Vladimir Čotrić2,4, Janko Pejović4 ,  Slavica  Mutavdžić  Divac11. Pediatric Hospital, Clinical Center Zemun, 2. Radiology Department, Clinical Center Zemun, 3. Clinical Center Zvezdara, 4. Sanitary medical school of applied sciences “VISAN Pneumococcal disease (PD) represents a spectrum of infections caused by Streptococcus pneumoniae. Isolation of Streptococcus pneumoniae from normally sterile areas and fluids is a key diagnostic method for Invasive pneumococcal disease (IPD). Despite the availability of conjugate vaccines, infections caused by non-vaccine serotypes have increased serious and invasive infection incidence („serotype replacement“).Case report: We present a 20-month-old male admitted with a six-day history of fever and respiratory symptoms. Chest radiography and ultrasound confirmed pneumonia with pleural effusion. Laboratory findings revealed significant elevated inflammatory markers (CRP 317 mg/L, PCT 3.43 ng/ml). Streptococcus pneumoniae serotype 19A was isolated from both blood culture and nasopharyngeal aspirate. It was susceptible to penicillins and cephalosporins but resistant to macrolides and aminoglycosides. The patient was successfully treated with empirical dual antibiotic therapy, followed by ceftriaxone monotherapy, resulting in full clinical and radiological recovery. Considering the incomplete vaccination, complete vaccination with the 13-valent vaccine was recommended.Discussion: Early recognition is essential for improved outcome, but often poses a challenge in pediatric practice: the symptoms are nonspecific with good condition, there are no specifically sensitive laboratory parameters that would indicate the severity or cause of the infection and sampling of microbiological material from the respiratory tract is limited. Early initiation of antibiotic therapy ensures a favorable outcome and reduc complications. In this case report non-vaccine serotype 19A was confirmed, which is consistent with the occurrence of “serotype replacement”.Conclusion: This case report demonstrates that IPD remain diagnostic and therapeutic challenge. Can be develop in immunocompetent children with incomplete pneumococcal vaccination and the initial symptoms are nonspecific (fever, lethargy, mild to moderate respiratory distress).Initial empirical therapy according to defined and updated protocols is the cornerstone of treatment and vaccination remains the most effective method for its prevention. Continuous monitoring of pneumococcal serotype distribution and antibiotic resistance is essential, as well as planning public health strategies.
Keywords: Streptococcus pneumoniae, invasive pneumococcal disease, pneumonia, sepsis, septicemia, serotype 19A, children, vaccination